Internalisasi Nilai Pendidikan Akhlak Al-Qur’an melalui Kitab Waṣayā al-Ābā’ lil-Abnā’ di Pondok Pesantren Al-YusufiyahWar-Ridwaniyah - Agung Julian Siregar; Mardian Idris Harahap; Nur Fadhilah Syam (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2026)
The contemporary moral crisis among Muslim youth demands strengthening strategies for internalizing Qur’anic moral values within educational institutions, drawing on the classical Islamic boarding school tradition. This study aims to analyze the structure of moral values ​​in the Waṣayā al-Ābā’ lil-Abnā’ Book, examine the internalization patterns applied at the Al-Yusufiyah War-Ridwaniyah Islamic Boarding School, examine the dialectic between normative texts and the context of educational practice, and identify the manifestations of values ​​in the lives of students. A qualitative approach is used with a field study design through participatory observation, in-depth interviews, and document analysis, and the data are then analyzed thematically and critically to find integrated patterns of meaning. The results of the study show that the structure of moral values in the book comprises dimensions of personal etiquette, social relations, and spiritual responsibility, which are internalized through habituation, exemplary behavior by kyai, repetition of texts, and social control rooted in Islamic boarding school culture. The dialectic of text and context shapes the transformation of values from normativity to ethical praxis, alive in the daily lives of students, as reflected in the discipline of worship, communication ethics, and collective awareness of the values of simplicity and respect. Academic contributions lie in strengthening the integrative model of value internalization, ​​based on turath’ books, that combines cognitive, affective, and practical dimensions, while also offering a new conceptual framework for the study of Islamic boarding school moral education oriented towards sustainable character formation.